High-Performance, Transparent Thin Film Hydrogen Gas Sensor Using 2D Electron Gas at Interface of Oxide Thin Film Heterostructure Grown by Atomic Layer Deposition - Kim, Sung Min; Kim, Hye Ju; Jung, Hae Jun; Park, Ji Yong; Seok, Tae Jun; Choa, Yong Ho; Park, Tae Joo; Lee, Sang Woon (Advanced Functional Materials, 2019)
A high-performance, transparent, and extremely thin (<15 nm) hydrogen (H 2 ) gas sensor is developed using 2D electron gas (2DEG) at the interface of an Al 2 O 3 /TiO 2 thin film heterostructure grown by atomic layer deposition (ALD), without using an epitaxial layer or a single crystalline substrate. Palladium nanoparticles (≈2 nm in thickness) are used on the surface of the Al 2 O 3 /TiO 2 thin film heterostructure to detect H 2 . This extremely thin gas sensor can be fabricated on general substrates such as a quartz, enabling its practical application. Interestingly, the electron density of the Al 2 O 3 /TiO 2 thin film heterostructure can be tailored using ALD process temperature in contrast to 2DEG at the epitaxial interfaces of the oxide heterostructures such as LaAlO 3 /SrTiO 3 . This tunability provides the optimal electron density for H 2 detection. The Pd/Al 2 O 3 /TiO 2 sensor detects H 2 gas quickly with a short response time of <30 s at 300 K which outperforms conventional H 2 gas sensors, indicating that heating modules are not required for the rapid detection of H 2 . A wide bandgap (>3.2 eV) with the extremely thin film thickness allows for a transparent sensor (transmittance of 83% in the visible spectrum) and this fabrication scheme enables the development of flexible gas sensors.
Keywords: 2-D electron gas (2DEG); Epitaxial interfaces; Hydrogen gas sensors; Oxide heterostructures; Palladium nanoparticles; Process temperature; Single crystalline substrates; Transparent thin film; atomic layer deposition; gas sensor; hydrogen; oxide heterostructure; thin film